Interactional functions of laughter in assisted reproductive medicine consultations - Bigi, Sarah; Tedone, Amanda; Vegni, Elena (Communication and Medicine, 2024)
Doctor –couple interactions in the context of assisted reproductive medicine frequently include occurrences of laughter, especially patient-initiated. These have been examined in previous studies from a quantitative perspective and in relation to specific topics, but not as regards the functions that laughter realises throughout the interactions. Our study aims to address this underinvestigated issue by providing an analysis of a small sample of consultations (n = 10) about assisted reproductive technology (ART) treatments. The analysis is set within a discourse-interactional perspective on clinical interactions, which focuses on consultations as advice-seeking activities in which advice-giving is the main discourse type. The consultations have been analysed through structural mapping, which has revealed five main phases: opening, information sharing, problem identification, discussion of the options and closing. Laughter tokens have been identified and their functions are described from the point of view of an incongruity-based framework. The interactional functions of laughter described in this framework, e.g., ‘marking incongruity’, ‘softening trouble-telling’, ‘showing sympathy’, ‘marking irony’ etc., have then been mapped onto the different phases of the consultations, yielding a fine-grained description of when laughter occurs and what participants are using it for. Our study expands on previous analyses of laughter in ART consultations, offering a novel methodological approach that could be applied to larger corpora.